2021
DOI: 10.1002/cncr.33182
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet and grade group progression in localized prostate cancer: An active surveillance cohort

Abstract: Background The Mediterranean diet (MD) may be beneficial for men with localized prostate cancer (PCa) on active surveillance (AS) because of its anti‐inflammatory, antilipidemic, and chemopreventive properties. This study prospectively investigated adherence to the MD with Gleason score progression and explored associations by diabetes status, statin use, and other factors. Methods Men with newly diagnosed PCa on an AS protocol (n = 410) completed a baseline food frequency questionnaire, and the MD score was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…In addition, over one-third of prostate cancer is slowly growing or progressing over several decades. This group of patients without cancer-related symptoms do not warrant aggressive, immediate treatment [2] . Instead, they are closely monitored for their indolent status using prostate-specific antigen (PSA) kinetics, periodic biopsies for histologic progression, and possibly surveillance magnetic resonance imaging (MRI) until further treatment is needed as judged by physicians.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, over one-third of prostate cancer is slowly growing or progressing over several decades. This group of patients without cancer-related symptoms do not warrant aggressive, immediate treatment [2] . Instead, they are closely monitored for their indolent status using prostate-specific antigen (PSA) kinetics, periodic biopsies for histologic progression, and possibly surveillance magnetic resonance imaging (MRI) until further treatment is needed as judged by physicians.…”
Section: Introductionmentioning
confidence: 95%
“…Instead, they are closely monitored for their indolent status using prostate-specific antigen (PSA) kinetics, periodic biopsies for histologic progression, and possibly surveillance magnetic resonance imaging (MRI) until further treatment is needed as judged by physicians. This emergent strategy for the management of indolent prostate cancer is called active surveillance [2] . Men on active surveillance have high anxiety, depression and doubts about the possible progression of the disease and are highly motivated to prevention approaches using dietary or pharmacological means or positive lifestyle changes [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, findings from Gregg et al have shown that adherence to the basic principles of the MD may lower the risk of Gleason grade progression among US men with localized PCa on active surveillance. 65 Further studies are needed to verify patient and cancer-specific effects of MD adherence in men with early-stage PCa. In addition, future studies should evaluate MD adherence with tools that include not only food consumption but also the evaluation of lifestyle factors and cultural subtexts.…”
mentioning
confidence: 99%